Development and validation of the antecedents to videoconference fatigue scale in higher education (AVFS-HE) - Li, Benjamin Junting (2024)
Despite the post-COVID return to face-to-face teaching and learning, many higher educational institutions continue to utilize videoconferencing due to its numerous benefits. Along with this increased adoption, reports have surfaced regarding videoconference fatigue (VF), a phenomenon characterized by exhaustion from using videoconference platforms. Despite this, there is a substantial gap in our understanding of the antecedent factors contributing to VF. Our study aims to develop and validate a research instrument for the study of the antecedents to VF in the context of whole-class teaching in higher education, which we term the AVFS-HE. We developed and tested this scale across three studies: first with 21 undergraduates in the substantive validity phase, and a further 508 undergraduates in the structural validity and external validity phases. The final 17-item AVFS-HE encompassed five key antecedents to VF: psychological, technical, social, productivity (engagement), and productivity (distraction) antecedents. The measure was shown to demonstrate good validity both internally and in relation to VF constructs. Recommendations for future research and practical recommendations for educators are discussed.